Monitoring of the geochemical evolution of waste rock facilities at Newmont’s Phoenix Mine - Keller, JM; Busker, LT; Milczarek, MA; Rice, RC; Williamson, MA (Mine Closure 2011: Sixth International Conference on Mine Closure, 2011)
Newmont Mining Corporation’s Phoenix Mine in Nevada, USA is actively reclaiming historic and current waste rock disposal areas with evapotranspiration (ET) covers to reduce the long-term risk of acid rock drainage. The waste rock is typically sulphide enriched and considered to be potentially acid generating (PAG). The total sulphide content of all waste material averages 2–3%, of which less than 20% is pyrrhotite with the remaining being a combination of pyrite and marcasite. There are pockets (often in the hundreds of tons range) of material that average greater than 50% sulphide. ET covers consist of nominal 2 m thick alluvial soil and/or non-PAG waste rock placed over the waste rock material. To monitor the ET cover’s capacity to store and release incident precipitation and the evolution of potential acid rock drainage generation in closed waste rock facilities, near surface (less than 3.5 m below ground surface) cover performance monitoring sensor nests and deeper subsurface geochemical evolution monitoring wells (to a maximum depth of 67 m) have been installed in the South Iron Canyon and North Fortitude rock disposal areas. Near-surface sensor nests and the geochemical evolution monitoring wells are instrumented at various depths with water content, water pressure potential, air pressure, oxygen concentration, temperature, and water flux sensors. These monitoring systems provide information on net percolation in the waste rock, air flow within the waste rock, and the relative oxidation of sulphide material at depth. In addition, the instrumentation has been designed to test hypotheses regarding the distribution and movement of water and air in “end dumped” lifts. Initial data indicates that the cover systems are effectively storing and releasing precipitation. Deep zones of elevated temperature within the waste rock have been identified and may indicate the presence of sulphide enriched waste rock being exposed to incident precipitation for prolonged periods during the disposal area construction phase. Three years of monitoring data will be presented to illustrate cover system performance and controlling factors in the geochemical evolution of the waste rock disposal areas.